FIRM SIZE DAN PROFITABILITAS DALAM MENENTUKAN FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2021 – 2023 - Fadhila, Rizki Ainun; Suartini, Sri; Sulistiyo, Hari (E-Jurnal Akuntansi TSM, 2026)
This study aims to analyze the effect of Firm Size and Profitability (ROA) on Financial Distress in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research employs a quantitative approach using multiple linear regression analysis. The sample consists of 10 companies selected through the purposive sampling method. Financial distress is measured using the Altman Z-Score model. The results indicate that Profitability (ROA) has a positive and significant effect on Financial Distress, while Firm Size shows no significant effect. However, both variables simultaneously have a significant influence on Financial Distress. These findings suggest that profitability plays a dominant role in determining the financial health of food and beverage companies in Indonesia.